Evaluating the Impact of Health Records Management on the Efficiency of Healthcare Delivery: A Study of Health Information Managers at University College Hospital, Ibadan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction and Objective: Efficient healthcare delivery relies heavily on the systematic management of patient health records, a process overseen by Health Information Managers (HIMs). In low- and middle-income countries such as Nigeria, persistent challenges in records management ranging from infrastructural deficits to policy gaps continue to undermine service efficiency. This study aimed to evaluate the impact of health records management on the efficiency of healthcare delivery among HIMs at University College Hospital (UCH), Ibadan, and to identify prevailing barriers to effective record-keeping.Methods: A descriptive cross-sectional design was employed, targeting Health Records Officers at UCH, Ibadan. Using convenience sampling, 200 respondents completed a structured, self-administered questionnaire capturing socio-demographics, current records management practices, perceived efficiency impacts, and encountered challenges. Data were analyzed using SPSS version 23, with descriptive statistics summarizing findings.Results: Respondents identified substantial challenges affecting records management, including data confidentiality and security concerns (98%), system integration issues (82%), technical limitations such as downtime (82%), and data quality problems (83%). Organizational barriers, including inadequate policy frameworks and resistance to change, were also reported by 81.5% of participants. Notably, respondents’ age and years of professional experience were significantly associated, suggesting a demographic trend relevant to workforce planning.Conclusion: The study underscores the critical role of effective health records management in promoting timely access to patient information, supporting clinical decision-making, and enhancing the coordination of care at University College Hospital, Ibadan. Findings highlight the need for continuous capacity building of Health Information Managers, investment in modern records management technologies, and strict adherence to data quality standards. Strengthening these areas can contribute to improved healthcare delivery outcomes and operational efficiency.